PENINGKATAN KAPASITAS PETANI DALAM PENGENDALIAN ORGANISME PENGGANGGU TANAMAN PADA BUDIDAYA CABAI MERAH DI KECAMATAN TUGUMULYO KABUPATEN MUSI RAWAS - Tri Novita Wulandari; Tri Ratna Saridewi; Dayat Dayat (Sekolah Tinggi Pariwisata Mataram, 2020)
This research was conducted to find a picture of the level of the capacity of farmers , know the factors that influence the level of farmers' capacity to control Pest Organisms Plants (OPT) in the cultivation of red peppers and formulate appropriate strategies to increase the capacity of farmers in controlling pests in the cultivation of red pepper . The research data was taken from open questionnaire instruments, field observations and interviews. Determination of the number of samples carried out by quota sampling that is 35 respondents . The data processing technique used is descriptive analysis and inference using multiple linear regression. Based on the results of the study, it can be concluded that the capacity of farmers in pest control is still relatively moderate due to the lack of farmers' ability to plan, implement pest control technology, ability to solve problems, the ability to evaluate and the ability to establish partners. Age factors, formal education, land area, length of farming, external factors and the factors of extension activities together have a positive influence on the level of capacity of farmers. The strategy that can be carried out to increase the capacity of farmers is to establish mentors or tutors who come from the farmers the mselves and are supported by adequate external factors and extension activities carried out intensively by extension agents